Comparison of Exotic Ispaghol (Plantago ovata Forsk.) Genotypes with the Local Variety ‘Gulabi’ - Khaskheli, Waheed Ali; Mangan, Bakht Nisa; Soomro, Aijaz Ahmed; Rajpar, Inayatullah; Lashari, Muhammad Siddique (Journal of Agriculture and Veterinary Science, 2026)
Sindh is the main hub of Ispaghol cultivation due to its favorable climate for its expansion. However, limited information is available on the morphology and genetic variability of Ispaghol, particularly with respect to its exotic genotypes. Focusing these outlines, two-year study was conducted during 2023-24 and 2024-25 at Tobacco and Medicinal Crop Research Institute, Tandojam (Sindh) Pakistan. Under this study, it was tried to screen out the adoption of high-yielding exotic varieties for improving Ispaghol yield in Sindh. Results of present study indicated that there was a great variability for morphological, physiological, yield parameters in exotic Ispaghol genotypes as compared to well adopted local variety Gulabi under Tandojam conditions for both studied years (2023-24 and 2024-25). Seed index, was ranged between 1.8 to 2.2g with average mean 2.0 g among exotic genotypes. The lowest 1000 (thousands) seeds weight was recorded in Gulabi (1.3 to 1.6 g). According to the findings four genotypes promising better seed yield kg ha-1 (from 874 to 1148kg ha-1) with the husk yield (225.7 to 330.9 kg ha-1) while as compared to local Gulabi with lower seed yield (679 kg ha-1) with husk yield (160 kg ha-1). The main conclusion arising from this study is that on the basis of seed yield per plant IELF-1, IELF-2, IELF-3 and IELF-4, can be chosen for commercial cultivation in Tandojam conditions over to local Gulabi.
Keywords: Ispaghol; Exotic genotypes; Growth; Yield